Analisis Daya Saing Serta Faktor-Faktor Yang Mempengaruhi Ekspor Bijih Nikel Di Indonesia - Setiawan, I Kadek Dian; Setiawina, Nym Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 8, No. 4, April 2019, pp (703-940), 2019)
Nickel ore is one of the export products from the mining sub-sector. This study aims to 1) determine the competitiveness of Indonesian nickel ore exports in 1995-2014, 2) find out whether the variables in this study which include the United States dollar exchange rate, production, IHPB and PMA simultaneously and partially affect the export of Indonesian nickel ore In 1995-2014, and 3) knew the dominant influencing variables. The data source used is secondary data. Data analysis techniques used Revealed Comperative Advantage (RCA) and multiple linear regression analysis. The results show that the average Indonesian RCA is 0.751 <1, so that it can be categorized as having weak competitiveness. The results of multiple linear regression analysis show that simultaneously the United States dollar exchange rate, production, IHPB and PMA have a significant effect on Indonesian nickel ore exports in 1995-2014. Partially the United States dollar exchange rate variable has significant and significant effect on nickel ore exports, while production, IHPB and PMA have a positive and significant effect on Indonesian nickel ore exports in 1995-2014. The most influential variable on Indonesia's nickel ore exports in 1995-2014 is the production variable.